ANALISIS DAYA PEMBEDA SOAL OPEN BOOK DI MASA PANDEMI MATA KULIAH STATISTIKA PENDIDIKAN - Khairul azmi; Sri Novia Martin (LP2M Universitas Adzkia, 2021)
During the pandemic STKIP Adzkia student learning was conducted online. The types of questions given to students are different from before the pandemic. During the Pandemic, the questions were given using the open book method. The open book method also affects the questions given to students. These questions are not questions of type C.1 and C.2, on bloom's taxonomy which they can easily find on the internet or in existing references. These questions must be questions that require answers that require arguments from students. Of course, these questions also need to be studied in depth whether these questions are able to distinguish students' abilities correctly and accurately. If the question is able to distinguish the student's ability, how accurately the question is able to distinguish the student's ability. How far is the quality of the questions in differentiating students' abilities? After analyzing the 8 items, there are 5 items that are valid and reliable. And the five questions were analyzed, it was found that the 5 items were questions with good distinguishing power.